(untitled) (Jurnal EurekaMatika, 2025)
This research aims to analyze and predict the popularity of the For Your Page (#fyp) on TikTok using time-series methods, specifically moving averages, to identify patterns, driving factors, and implications for digital marketing strategies. Data was collected from the Exolyt platform for 14 days (April 12-25, 2025), with daily impression counts measured. The analysis showed significant fluctuations (32.9-56.3 billion impressions) with a weekly cyclical pattern, where user engagement increased on weekends. The 3-day moving average method successfully smoothed out the random fluctuations and showed a trend decline (April 14-23) and recovery (April 19-25). The findings confirm the influence of temporal factors, viral content, and the TikTok algorithm. Practically, we recommend weekend posting optimization and real-time monitoring using time-series analysis while contributing to adaptive predictive models for data.